PERTUMBUHAN DAN PERKEMBANGAN TANAMAN SAMAMA (Anthocephalus macrophyllus) DI DEMPLOT SUMBER BENIH DESA HATUSUA KECAMATAN KAIRATU KABUPATEN SERAM BAGIAN BARAT - Yali Joko Istia, Yali Joko Istia; Siahaya, Ludia; Irwanto, Irwanto (MARSEGU : Jurnal Sains dan Teknologi, 2024)
The aim of this research is to determine the diameter increment and height increment, growth and development of Samama Plants (Anthocephalus marcophyllus) as well as environmental factors that influence the growth of Samama Plants (Anthocepalus marcophyllus). This research was carried out in Block III of Samama Plants (Anthocephalus marcophyllus) in the Seed Source Demonstration Plot in Hatusua Village, Kairatu District, West Seram Regency. Initial data was taken in January 2022 and continued with final data collection in July 2022. This research uses a quantitative analysis method by calculating the Average Annual Increment (MAI), current annual increment (CAI) and analysis simple regression. The results of further research show that the growth of Samama (Anthocephalus marcophyllus) plants in the seed source demonstration plot of Hatusua village, West Seram Regency with a Current Annual Rate (CAI) diameter in 2022 is 1.2 (cm/tnm/yr) and an average annual increase (MAI) diameter is 3.05 (cm/tnm/yr), current annual increment (CAI) is high, namely 1.77 (m/tnm/yr) and average annual increment (MAI) is high, namely 2.93 (m /tnm/yr). The development of the Samama plant in measurements in 2022, the walnut plant has developed. From the results of research in 2022, the growth of the Samama plant is at the pole and tree level. There are 8 trees on the pole with diameters ranging from 14.5 – 20.